2005
DOI: 10.1530/eje.1.01954
|View full text |Cite
|
Sign up to set email alerts
|

Expression of renal 11β-hydroxysteroid dehydrogenase type 2 is decreased in patients with impaired renal function

Abstract: Objective: Renal 11b-hydroxysteroid dehydrogenase type 2 (11b-HSD2) enables selective access of aldosterone to the mineralocorticoid receptor (MR). Impaired 11b-HSD2 activity has been suggested in patients with hypertension as well as in patients with renal disease, where it may contribute to sodium retention, oedema and hypertension. To date, these studies have relied upon urinary cortisol (F) metabolite levels as surrogate markers of renal 11b-HSD2 activity. Methods: We have directly analysed renal 11b-HSD2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
48
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 50 publications
5
48
1
Order By: Relevance
“…Additionally, administration of isotope-labeled tracers might influence endogenous cortisol production by negative feedback (18). However, it has been shown that determination of urinary excretion rates of the major endogenous glucocorticoid metabolites presents a suitable alternative to isotopic methods for the determination of cortisol secretion (15,19,50) and gas chromatography-mass spectrometry (GC-MS) urinary steroid profiling has been successfully used in determining cortisol secretion in preterm infants (14).Meanwhile, measurement of urinary 24-h major cortisol metabolites is an established method used by numerous endocrine research groups (9,16,23,29,39,41,43,49) to examine adrenocortical activity and/or glucocorticoid metabolism in healthy and ill children and adults. This relies on the fact that the sum of the seven major urinary cortisol metabolites (for details see SUBJECTS AND METHODS) encompasses almost 80% of the cortisol secreted per day by the adrenal gland (27,40).…”
mentioning
confidence: 99%
“…Additionally, administration of isotope-labeled tracers might influence endogenous cortisol production by negative feedback (18). However, it has been shown that determination of urinary excretion rates of the major endogenous glucocorticoid metabolites presents a suitable alternative to isotopic methods for the determination of cortisol secretion (15,19,50) and gas chromatography-mass spectrometry (GC-MS) urinary steroid profiling has been successfully used in determining cortisol secretion in preterm infants (14).Meanwhile, measurement of urinary 24-h major cortisol metabolites is an established method used by numerous endocrine research groups (9,16,23,29,39,41,43,49) to examine adrenocortical activity and/or glucocorticoid metabolism in healthy and ill children and adults. This relies on the fact that the sum of the seven major urinary cortisol metabolites (for details see SUBJECTS AND METHODS) encompasses almost 80% of the cortisol secreted per day by the adrenal gland (27,40).…”
mentioning
confidence: 99%
“…Importantly correlations between the ratios of cortisol to cortisone metabolites, (THF + 5aTHF/THE) and F/E as index markers of the activities of 11β-HSD1 and 2, respectively, [22,23], and various clinical and laboratory parameters of disease activity were found (Figures 3 and 4). These correlations present evidence, that the enzyme activities are regulated by the disease activity (Figures 3 and 4).…”
Section: Resultsmentioning
confidence: 90%
“…Impaired activity of this isozyme has been demonstrated in hypoxia (19) and in renal disease (20,21), syndromes that develop with abnormal handling of potassium and sodium and high blood pressure. These observations led us to hypothesize that the decreased 11β-HSD2 may improve the access of glucocorticoids to mineralocorticoid receptors, leading to hypertension and Na + retention.…”
Section: Discussionmentioning
confidence: 99%